2018
DOI: 10.1002/anie.201713206
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Activation of Sulfur Hexafluoride: Metal‐Free, Selective Degradation by Phosphines

Abstract: The development of new methods for the chemical activation of the extremely inert greenhouse gas sulfur hexafluoride (SF ) not only is of current environmental interest, but also offers new opportunities for applications of SF as a reagent in organic synthesis. We herein report the first nucleophilic activation of SF by Lewis bases, namely by phosphines, which results either in its complete degradation to phosphine sulfides and difluorophosphoranes or in the selective conversion of SF into a bench-stable, crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 38 publications
2
58
0
1
Order By: Relevance
“…However, formation of the C−S bond still requires the use of extraordinarily toxic reagents, like S 2 F 10 , and the mixed‐sulfur halogenides SF 5 Cl and SF 5 Br. In contrast, reports on non‐toxic SF 6 in synthesis are rare although this would have strong environmental advantages . SF 6 is still indispensable as an insulating gas in technical applications, like high‐voltage gears, and as a protecting gas in the production of metals.…”
Section: Figurementioning
confidence: 99%
“…However, formation of the C−S bond still requires the use of extraordinarily toxic reagents, like S 2 F 10 , and the mixed‐sulfur halogenides SF 5 Cl and SF 5 Br. In contrast, reports on non‐toxic SF 6 in synthesis are rare although this would have strong environmental advantages . SF 6 is still indispensable as an insulating gas in technical applications, like high‐voltage gears, and as a protecting gas in the production of metals.…”
Section: Figurementioning
confidence: 99%
“…We recently showed that tris(1‐butylpyridin‐4‐ylidenamino)phosphine can be generated in situ from the reaction of 1‐butylpyridin‐4‐imine with PCl 3 and subsequent treatment with potassium bis(trimethylsilyl)amide (KHMDS) . However, our attempts to isolate the phosphine were unsuccessful due to the formation of stable coordination compounds between the exocyclic N atoms of the pyridin‐4‐imine moieties and KCl formed in the reaction.…”
Section: Figurementioning
confidence: 99%
“…Recently, we discovered that the electron‐donating ability of phosphines can be significantly increased, beyond the range of N‐heterocyclic carbenes, by attaching up to three strong π‐donating imidazoline‐2‐ylidenamino substituents to the phosphorus atom . The resulting phosphines are promising ligands in catalysis and can activate and transform chemically rather inert species such as CO 2 or SF 6 …”
Section: Figurementioning
confidence: 99%
“…As indicated above, it has been shown by groups of Beier, Dielmann, Kirsch, Roeschenthaler, Rueping, and Wagenknecht that SF 6 can be converted into SF 5 − or organo SF 5 compounds originating from styrene derivatives . In another approach at transition‐metal complexes, it was demonstrated at platinum that SF 6 can also be transformed into a SF 3 building block.…”
Section: Sulfur(vi) Compoundsmentioning
confidence: 94%